2021
DOI: 10.35765/mjse.2021.1019.06
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Collective Efficacy as a Predictor of Students’ Academic Performance in North Central Nigeria

Abstract: Public secondary schools in Nigeria occupy a significant position for providing qualitative education, yet there has been increasing public discontent with the quality of students being produced in the country’s public secondary schools. Teachers are regarded as one of the resources necessary for achieving the goals of secondary education. It is against this backdrop that this study examined teachers’ collective efficacy as a predictor of students’ academic performance in North Central Nigeria. Three research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results of the present study showed that teacherstudent interaction is related to academic enthusiasm both directly and indirectly through academic hope and academic self-regulation. This finding is with the results of (Ibrahim et al, 2022;Jung and Ryu, 2022;Samadieh and Sadri, 2022) are aligned. In their research, Martin and Marsh (2006) concluded that academic enthusiasm has an inverse relationship with anxiety and a direct relationship with teacher-student interaction, self-regulation, and academic engagement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the present study showed that teacherstudent interaction is related to academic enthusiasm both directly and indirectly through academic hope and academic self-regulation. This finding is with the results of (Ibrahim et al, 2022;Jung and Ryu, 2022;Samadieh and Sadri, 2022) are aligned. In their research, Martin and Marsh (2006) concluded that academic enthusiasm has an inverse relationship with anxiety and a direct relationship with teacher-student interaction, self-regulation, and academic engagement.…”
Section: Discussionsupporting
confidence: 90%
“…Academic enthusiasm refers to behaviors that are related to learning and academic achievement (Ibrahim et al, 2022). In theories of learning, motivation and passion are a combination of behavioral and cognitive approaches (Grohman and Snyder, 2022).…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to Ibrahim et al (2022) teachers' OCB is a tool through which they can attain efficacy, which will lead to outstanding performance. According to the findings of Arokiasamy et al (2022) study, TL has a positive impact on OCB.…”
Section: Influence Of Tl On Ocbmentioning
confidence: 99%